Education made with passion: experience for teaching practice in community education project integrar - Santos, Larissa Anjo; Firmino, Larissa Corrêa; Martins, Rosa Elisabete Militz Wypyczynski (Geosaberes, 2017)
This article aims to report on the activities carried out in teaching practice held through the discipline of Supervised internship in geography III in the first half of the year of 2017, this discipline of the course of degree in Geography from the University of the State of Santa Catarina (UDESC). The text contains bibliographic surveys to stimulate discussion about the adult education (EJA), first of historical and documentary stamp and, subsequently, on the training of teachers for this area. In addition to the description of the Community education project Integrar (stage field) and teaching practice. At the end of the internship, it was not only the importance of the work of future teachers in the field of EJA, but an act which integrates and understand the particularities of this mode of teaching.
Keywords: EJA; Estágio docente; Geografia; Formação de professores.